THE DERIVATION OF LEXICAL NORM - Mamatkulova Saidaxon (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
The current stage of linguistic development is undoubtedly the era of studying the meaning of words. One of the main issues in the field of linguistics arises from the fact that human language, in its primary function, serves as a tool for communication, encoding, and disclosing certain information. The gradual development of this thesis has led to the acknowledgment that linguistics, including semantics—a discipline that focuses on lexical meaning—has unfortunately been overshadowed by grammatical content due to frequent misunderstandings. It is no coincidence that lexical-semantic dictionaries have become an essential part of describing language. Moreover, theoretical dictionaries that provide comprehensive semantic definitions of linguistic units serve as a basis for defining linguistic concepts with precision, which are foundational for the semantic harmony and distinctions of language objects.